Dominant factors of SMEs failure - multigroup confirmatory factor analysis - Milošević, Isidora; Mihajlović, Ivan; Stojanović, Anđelka (Serbian Journal of Management, 2019)
The paper aims to provide empirical clarification over some key failure factors of Small and Medium-sized Enterprises (SMEs), and also analysis of the similarities and differences in factors’ relations in the Republic of Serbia and Visegrad countries. The SMEs’ failures factors have been accessed from the point of view of SMEs owners and managers whose opinions were collected through a questionnaire disseminated in five countries (Hungary, Czech Republic, Slovak Republic, Poland and the Republic of Serbia). On the other hand, for the research presented in this paper, the data from Hungary, the Czech Republic and the Republic of Serbia were used. The structural equation model was developed and analyzed to confirm the reliability of the conceptual model, using multi-group confirmatory factor analysis (MGCFA) for comparative measurements on the observed data from different countries. The result showed the existence of differences in opinions of SMEs owners and managers concerning failure factors in examined countries.